PROCESS DESIGN OF BATHYMETRIC, WATER LEVEL, AND SURFACE CURRENT DATA CONVERSION ACCORDING TO IHO S-100 STANDARD AS PART OF ENC CELL NUMBER 293 - Daffa Rizki El-Islami, Muhammad
With the advent of Electronic Navigational Charts (ENC) since the International Hydrographic Organization (IHO) released the S-57 standard in 1992, digital hydrographic data has become a critical element in ensuring safety in marine navigation. In response to the developments in the geospatial information world, IHO released the S-100, a new universal hydrographic data model designed to be compatible with the latest geospatial data standards. IHO S-100 supports a wide range of hydrographic data applications, including bathymetric surface, water level, and surface current data. Presently, the S-100 is not yet widely known and implemented by the hydrographic industry, and its use is limited to national hydrographic offices. The establishment of best practices in the conversion of S-100 datasets is necessary to accelerate the adoption of the standard by the wider hydrographic community. This project aims to design a process to produce digital hydrographic data, i.e., bathymetric surface, water level, and surface current data conformant to the IHO S-100 series of product specifications. A conversion process is formulated as the product of this project, complete with the design criteria and a toolbox for conversion of the S-100 datasets. The process consists of four stages: initial data processing, structuring, attribution, and testing. The conversion tools used are primarily in the Python programming language, and testing is done using S-100 Viewer software. ENC number 293 covering the Alas Strait in West Nusa Tenggara is used in the example of hydrographic datasets produced in this project, complete with the S-100 data file and portrayal visualization. This project also highlights the implementation potential of the production of S-100 datasets based on the rate of marine traffic in ENC 293.